1994
DOI: 10.1146/annurev.mi.48.100194.003101
|View full text |Cite
|
Sign up to set email alerts
|

Mscramm-Mediated Adherence of Microorganisms to Host Tissues

Abstract: Microbial adhesion to host tissue is the initial critical event in the pathogenesis of most infections and, as such, is an attractive target for the development of new antimicrobial therapeutics. Specific microbial components (adhesins) mediate adherence to host tissues by participating in amazingly sophisticated interactions with host molecules. This review focuses on a class of cell surface adhesins that specifically interact with extracellular matrix components and which we have designated MSCRAMMs (microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
786
2
19

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,049 publications
(827 citation statements)
references
References 77 publications
9
786
2
19
Order By: Relevance
“…These molecules enable bacteria to bind to different extracellular matrix proteins with which foreign-body materials, such as sutures, are coated shortly after they are introduced into the human body. [41][42][43] The microbial characteristics of an implanted medical device, therefore, depend in the first instance on its affinity for such proteins. Concerning direct binding of bacteria to surfaces, interspecies comparison showed that pathogens tend to be hydrophobic 44 and that their hydrophobic properties decide whether bacteria preferably bind to hydrophobic or to hydrophilic surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules enable bacteria to bind to different extracellular matrix proteins with which foreign-body materials, such as sutures, are coated shortly after they are introduced into the human body. [41][42][43] The microbial characteristics of an implanted medical device, therefore, depend in the first instance on its affinity for such proteins. Concerning direct binding of bacteria to surfaces, interspecies comparison showed that pathogens tend to be hydrophobic 44 and that their hydrophobic properties decide whether bacteria preferably bind to hydrophobic or to hydrophilic surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, vascular endothelium is resistant to the attachment of bacteria, but blood flow at high shear rates across heart valves can damage the protective endothelial cell layer, exposing blood to extracellular matrix and tissue factor, which initiates blood coagulation. Vascular injury concurrent with S. aureus bacteremia can lead to ABE, with infection initiated by microbial attachment to plasma or extracellular matrix proteins, including fibrinogen, fibronectin, von Willebrand factor (vWf), collagen, elastin and laminin [9,10]. Histology of S. aureus vegetations rarely shows leukocyte infiltration, due in part to bacterial secretion of anti-inflammatory factors [11].…”
Section: Acute Bacterial Endocarditismentioning
confidence: 99%
“…Absorbed fibronectin (Fn) is targeted by bacteria as an anchoring point for adhesion and invasion of epithelial cells [3,[10][11][12]. Hydrogen bonding [13], electrostatic interactions [14], specific interactions between surface proteins and extracellular matrix proteins [11,15,16], and shear forces [17] all have been shown to mediate bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonding [13], electrostatic interactions [14], specific interactions between surface proteins and extracellular matrix proteins [11,15,16], and shear forces [17] all have been shown to mediate bacterial adhesion. GBS will only adhere to adsorbed Fn, not soluble Fn1, 18,19; this behavior helps GBS evade the host immune system since soluble Fn acts as an opsonin [20].…”
Section: Introductionmentioning
confidence: 99%